Prevalence of Negative Exploratory Laparotomy in Some the Hospitals of Al-Russafa Side of Baghdad City (Indian Journal of Forensic Medicine & Toxicology, 2020)
Not all abdominal trauma need laparotomy thus this study has been conducted to evaluate the prevalenceof negative laparotomy in some of the hospitals of Al-Russafa side of Baghdad city. A retrospective crosssection study was be conducted in four hospital (Baghdad Teach hospital, Al-kindy, Al-sadder, Al-emam Alihospital) in Baghdad city. The period for data collection are (8) months from February to September 2014.Data was analyzed using the SPSS.This study revealed that the distribution of –ve labratomy are ( 6) for AL-Sadder hospital and (4) for otherhospitals in sample with (12%) for Al-sadder hospital ,(11.76 %) for Al-emam Ali and Baghdad hospitals,and (8) for Al –kindy hospital,The results of this study indicated that one ten of all expletory lapratomy wasnegative lapratomy. The prevalence distribution of expletory lapratomy are difference between hospitals ofAl-russafa and also there is difference in the prevalence of –ve expletory lapratomy among these hospitals.Based on this study Reliance on algorithm for patients with abdominal trauma should be to identify injuriesrequiring surgical repair, and to avoid unnecessary laparotomy. In addition provide imaging modalities andother investigative techniques in all hospitals and training of medical staff working in hospitals on focalassessment sonography for trauma program(FAST).